(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the determinants of the stock price of the impact of profitability, debt to equity ratio and sales growth in the automotive sub sector companies and its components listed on the Indonesia Stock Exchange in the period 2015-2019. Method This research uses quantitative verification analysis, panel data regression analysis test using purposive sampling method obtained a sample of 12 companies in the automotive sub sector and its components listed on the Indonesia Stock Exchange for the period 2015-2019. The results showed profitability had no effect on stock prices, the result was 0.4551, debt to equity ratio had an effect on stock prices, that is 0.0411 and sales growth had no effect on stock prices with a yield of 0.7834.